TRANSPARENCY OF NATIONAL BUDGET AND POVERTY REDUCTION: A CASE STUDY (Proceedings of the International Conference on Poverty and Sustainable Development, 2018)
National budget is the key document for every country indicating the country’s financial health by depicting past performance and highlighting future aspirations and emphases in line with national goals and development agenda. Even two-three decades back transparent and inclusive budgeting process was considered not the right thing to do. Accordingly, national budgets were drafted and managed by the finance ministry in a cautious, non-inclusive way by leaving out civil society and other non-government actors. Now fiscal transparency is widely advocated by major international institutions such as the International Monetary Fund, the World Bank, and the Organization for Economic Co-operation and Development and practiced by most of the countries across the globe. Improved fiscal transparency has also enhanced inclusiveness. This is especially significant for developing and under-developed countries whose most important target is economic growth coupled with poverty reduction. The Open Budget Survey takes into account factors such as the amount, level of detail, and timeliness of budget information governments make publicly available to assess a country’s budget transparency. This paper aims to reinstate the positive correlation between enhanced transparency of national budget and poverty reduction taking Bangladesh – a Lower Middle Income Country – as an empirical case.
Keywords: fiscal transparency; national budget; poverty reduction